2020
DOI: 10.1002/ajp.23216
|View full text |Cite
|
Sign up to set email alerts
|

Human engagement and great ape conservation in Africa

Abstract: Despite large investments of funding into great ape conservation in Africa, wild populations of gorillas (Gorilla ssp), chimpanzees (Pan troglodytes ssp) and bonobos (Pan paniscus) continue to decline. Causes for this decline fall into three broad categories: habitat loss, illegal hunting, and disease. Contributing factors to all of these causes are linked to pressure from the expanding human population competing for forest resources. We have moved beyond the time of debating the pros and cons of including hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Great apes, other nonhuman primates, and their habitats are under heavy pressure from a growing human population, and this conflict is expected to only intensify in coming years (Estrada et al, 2017). Engaging with local communities to solve for human–primate coexistence is a major, complex challenge, but one that is considered imperative for conservation to succeed (Bettinger et al, 2020, this volume). Funding and human resources are limited, however, so conservation efforts generally, and human behavior change projects specifically, must prioritize interventions where change is most needed and success is likely.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Great apes, other nonhuman primates, and their habitats are under heavy pressure from a growing human population, and this conflict is expected to only intensify in coming years (Estrada et al, 2017). Engaging with local communities to solve for human–primate coexistence is a major, complex challenge, but one that is considered imperative for conservation to succeed (Bettinger et al, 2020, this volume). Funding and human resources are limited, however, so conservation efforts generally, and human behavior change projects specifically, must prioritize interventions where change is most needed and success is likely.…”
Section: Discussionmentioning
confidence: 99%
“…This type of iterative evaluation and troubleshooting requires time and effort and, ultimately, human resources. Bettinger et al (2020, this volume) found that a limiting factor to whether human engagement initiatives of African ape projects were evaluated was whether the projects had dedicated education teams. Our campaign and follow‐up support was done in one village and over a relatively short period of time (3 years total), but that still required many months of intensive work by GRACE's full‐time, four‐person education team.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improper evaluation of success and nonholistic collaborations can worsen wildlife vulnerability despite much involvement from communities to create work plans with conservation organizations (Bettinger et al. 2021 ). Without genuine remorse and introspection for violence by colonial power paradigms, community collaboration and the insensitivity of negative legacy effects can reproduce harm, especially in areas where high conservation is abutted by colonialism-induced poverty (Petts 2007 ).…”
Section: Overcoming Place-based Biasmentioning
confidence: 99%
“…Undoubtedly this is done with the best intentions, for example “If only local people knew what we know, they would realise how important this primate/habitat is and stop their harmful practices.” But education frequently echoes a colonialist narrative and implies that certain types of knowledge are more valid than others. Not only is this attitude disrespectful, but there is a danger that education given without full understanding of the local cultural and social context may be offensive, ignored as worthless, or potentially culturally destructive (Bettinger et al, 2021 ; Bettinger & Leighty, 2021 ; Wallis & Lonsdorf, 2010 ). Such an approach can be counter-productive, in that local people may become alienated or unwilling to engage with conservation efforts.…”
Section: Knowledge and Educationmentioning
confidence: 99%